(3eUHGM GdCfGe aj TQM TQGjY GdESdGes - (3GdHOjQj GdfLaj, LYaQ Hf CMeO Hf Sja, J (B1369 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B.. (3bhdg cJGH GdTaYI hgj GSJMbGb CMO GdTQjcjf MUI TQjcg HSHH GfJbGdgG HGdHjY , Cbhd GdXGgQ Cf ZQV GdeUfa hZjQg ef GeJKGd gPG GdJYQja hfMhg EfeG gh GdJejR aj GdLedI adG jfHZj GdEWfGH ajgG (B...s
(3BNQgG (B:s
.. (3GdCTgQ ef GNJUGU GdTaGYI HGdHjhY hbO JbOe GdcdGe aj Pdc (B... (3hJeGe GdebUO GdNGeS GdPj gh aj GdTGQY ehchd Edi cJGH GdbVGA aEfg GdeJcad dPdc hCeKGdg (B.. (3hGdMeO ddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3Gd`CYdGe (B2/121s
(3GdPQjYI (B21 / 68 ( 4132)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis